GATE/Geant4 simulation of key dosimetric correction factors for alanine dosimetry in 12 C ion beams - Pascal Saße; Jessica Stolzenberg; Kilian-Simon Baumann; Vanessa Delfs; Ralf-Peter Kapsch; Hugo Palmans; Bjoern Poppe; Hui Khee Looe (Physics in Medicine & Biology, 2026)
Abstract Objective: Alanine has been used frequently as a reference dosimeter in clinical dosimetry. However, its high LET dependence poses a challenge for practical applications. Determination of the required beam quality correction factors requires Monte Carlo simulations. This makes the application of alanine infeasible if dedicated Monte Carlo tools or computing resources are not available. This work sets out to determine generalized alanine correction factors in clinical 12 C beams. Approach: Mathematical expressions were established to parametrize dosimetric correction factors. Spectral fluences in 429 MeV/u mono energetic and a range modulated 278 MeV/u 12 C beams were simulated at multiple depths along the central beam axis using GATE/Geant4. Beam quality correction factors were determined under Spencer-Attix conditions in water and in alanine-paraffin pellets. Main results: Analytical expressions for the water-to-medium stopping-power ratios and the beam quality correction factor were obtained. The analytical expressions represent correction factors that are well within the confidence interval, except at the Bragg peak and the distal edge of the SOBP.These points were found to be unsuitable for measurement using alanine standard dosimeters due to the high perturbation factors. Significance: The results allow alanine dosimetry to be performed for mono-energetic and range-modulated beams without prior Monte Carlo simulations. This greatly reduces the effort associated with practical alanine dosimetry.